2016
DOI: 10.1111/jace.14174
|View full text |Cite
|
Sign up to set email alerts
|

Excellent Transmittance Induced Phase Transition and Grain Size Modulation in Lead‐Free (1–x)(K0.5Na0.5)NbO3xLaBiO3 Ceramics

Abstract: A novel lead-free excellent transmittance electro-optic ceramics (1-x)(K 0.5 Na 0.5 )NbO 3 -xLaBiO 3 (KNN-LB, x = 0.000, 0.005, 0.010, 0.015, 0.020, 0.025, 0.040, 0.060) were fabricated by traditional pressureless ceramics processing procedure. The effects of LaBiO 3 dopant concentration x on the microstructure, phase transition, optical property, and electrical properties were studied systematically. The X-ray diffraction results indicated that the KNN-LB ceramics with x ≥ 0.025 have the pseudocubic phase. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 27 publications
2
36
0
Order By: Relevance
“…At higher values of x , the ceramics continually display reduced grain size to approximately 0.2 μm. Similar results were also reported in a series of A(B'B”)O 3 ‐modifed KNN ceramics . Although several explanations have been proposed, the origin of such submicron‐grains in A(B'B”)O 3 ‐modified KNN ceramics is still unclear.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…At higher values of x , the ceramics continually display reduced grain size to approximately 0.2 μm. Similar results were also reported in a series of A(B'B”)O 3 ‐modifed KNN ceramics . Although several explanations have been proposed, the origin of such submicron‐grains in A(B'B”)O 3 ‐modified KNN ceramics is still unclear.…”
Section: Resultssupporting
confidence: 84%
“…In addition, complex perovskite A(Bʹ, Nb)O 3 (A = Sr 2+ , Ca 2+ , and Ba 2+ ; Bʹ = Mg 2+ , Zn 2+ , and Sc 3+ ) substituted KNN ceramics with submicron grain size were found to simultaneously show high transmittance and reasonable dielectric and ferro‐/piezoelectric properties. The effectiveness of this strategy was confirmed in many systems by different and independent research groups, as listed in Table …”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…The calcining was accomplished at a temperature of 850‐900°C for 5 hours (850°C in this work), and sintering was performed at 1160‐1180°C for 6 hours (1180°C in this work). The intermediate steps, including milling, granulating, and pressing into a plate‐shape were also performed in the same manner as previously outlined . The optical transmittance, crystal structure, detailed microstructure, dielectric property and ferroelectric performance were characterized in the same manner as reported previously …”
Section: Methodsmentioning
confidence: 99%
“…However, almost all the KNN‐based ferroelectric ceramics examined in previous studies do not satisfy the requirement of both high optical transmittance and high energy storage density. Tables and show the visible optical transparency and energy storage density of most KNN‐based ceramics studied during the 2014‐2017 time period . It was found that transparent ferroelectric ceramics with high energy storage densities have rarely been created in previous studies.…”
Section: Introductionmentioning
confidence: 99%